READING FEMINISM VOICES IN SELECTED POETRY BY AUDRE LORDE - Haryantoni, Wiwin (LITERARY CRITICISM, 2014)
This paper deals with the feminism voices as reflected in selected poems of Audre Lorde. In this study, the researcher used the descriptive analysis with a lens of black feminist concept. The main focus of this study is the study of women oppression due to the power patriarchy in society and domestic area. This study will be materilized with the selection of Audre Lordeâs poems suchÂ as A Woman Speaker (1968), For Each Of You (1968), Now (1968), Love Poem (1973), Coal (1976), The Black Unicorn (1978), Who Said It Was Simple (1978), and Power (1982). The result of analysis showed that Audre Lorde challenged patrirchal oppression and supports his women to define their status and freedom under determination of male. Â Keywords: Audre Lordeâs poems, feminism, black feminism, women Â Â oppression.